On the Electromagnetic Vacuum Origins of Dark Energy, Dark Matter, and Astrophysical Jets - Stuart Marongwe (Advances in High Energy Physics)
We use a semiclassical version of the Nexus paradigm of quantum gravity in which the quantum vacuum at large scales is dominated by the second quantized electromagnetic field to demonstrate that a virtual photon field can affect the geometric evolution of Einstein manifolds or Ricci solitons. This phenomenon offers a cogent explanation of the origins of astrophysical jets, the cosmological constant, and a means of detecting galactic dark matter.